2004
DOI: 10.1158/1078-0432.ccr-1096-03
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Level of Transforming Growth Factor β1 Measured from the Azygos Vein Predicts Prognosis in Patients with Esophageal Cancer

Abstract: Experimental Design: Fifty-seven plasma samples were obtained intraoperatively from the azygos vein in patients with esophageal cancer. ELISA was used to quantify the plasma TGF-␤1 levels, which were correlated with pathological features and patient survival.Results: The mean plasma TGF-␤1 level measured from the azygos vein of esophageal cancer patients was 5.09 ؎ 0.48 ng/ml (mean ؎ SE). The survival rates of patients with a high TGF-␤1 level (defined as a level above the 4.6 ng/ml level of normal controls) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
(30 reference statements)
5
16
1
Order By: Relevance
“…Concentration of serum TGF-β1 in total ESCC patients, oesophagectomy and palliation groups and control group are significantly higher in T4 than T1 + T2 primary tumours extension. These data are consistent with previous ones [21,22] demonstrating, that plasma TGF-β1 level in ESCC patients has been increasing along with the tumour progression. A similar relationship has been found between tissue TGF-β1 level and depth of tumour invasion in gastric and lung cancers [7,12,24].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Concentration of serum TGF-β1 in total ESCC patients, oesophagectomy and palliation groups and control group are significantly higher in T4 than T1 + T2 primary tumours extension. These data are consistent with previous ones [21,22] demonstrating, that plasma TGF-β1 level in ESCC patients has been increasing along with the tumour progression. A similar relationship has been found between tissue TGF-β1 level and depth of tumour invasion in gastric and lung cancers [7,12,24].…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have reported that there was no relationship between sTGF-β1 levels and disease progression [14,21]. However, in our study, serum levels of TGF-β1 tended to be higher in advanced oesophageal cancer than those in stage I and II.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…2A). The physiological concentration of 1 ng/ml TGFB1 (Fukuchi et al, 2004;Kiliç et al, 2009;Ouellete et al, 2005;Villar et al, 2009) seemed to be maximally effective for phosphorylation of SMAD2 and SMAD3. Time-course experiments revealed that both SMAD2 and SMAD3 were phosphorylated within 5 minutes following treatment with TGFB1 (1 ng/ml) (Fig.…”
Section: Tgfb1 Induces Phosphorylation Of Smad2 and Smad3 In Clendo Cmentioning
confidence: 98%
“…This evidence was reinforced in a intraoperative study of the mean levels of TGF-1 from the azygos vein in patients with esophageal cancer, as higher levels significantly correlated with poorer survival. However, the majority of these cancers were esophageal squamous cell carcinoma, as opposed to adenocarcinoma (Fukuchi et al, 2004). The APC gene, a biomarker well known for its relationship with colon adenocarcinoma, has also been studied in esophageal carcinomas.…”
Section: Prognostic Value Of Biomarkersmentioning
confidence: 99%